Intellectual returnees as drivers of indigenous innovation: Evidence from the Chinese photovoltaic industry. (14th August 2017) - Luo, Siping; Lovely, Mary E.; Popp, David
Abstract: We offer new evidence on indigenous innovation and intellectual returnees by estimating the relationship between patenting activity by Chinese photovoltaic firms and the presence of corporate leaders with international experience. Our research approach combines data from three sources: the industrial census, international and domestic patent records, and leadership biographical information. Using non‐linear methods, we find robust evidence that returnees positively influence patenting activity and promote neighbouring firm innovation. Our analysis suggests that market liberalisation and industry policy influence patent application counts. Controlling for R&D expenditures, we find that firms with returnees in leadership roles do more patenting.